2022
DOI: 10.3390/app12042113
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of Abdominal Aortic Aneurysms with Severely Angulated Neck Based on Transient Hemodynamics Using an Idealized Model

Abstract: An abdominal aortic aneurysm (AAA) is an enlargement of the abdominal aorta that can become a life-threatening disease. The pulsatile blood flow exhibits intricate laminar patterns in the abdominal portion of the human aorta under normal resting conditions, whereas secondary flows are caused by adjacent branches and abnormal vessel geometries. If a pathological disorder (e.g., aneurysm) alters the structural composition of the artery wall, the flow dynamics become more complex. In this study, we analyzed the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…EVAR within a hostile neck anatomy, particularly in short and severe neck angulation, is associated with poor early and late outcomes [ 3 , 5 ]. One study of AAA with severely angulated necks revealed significant changes in velocity, flow streamline, pressure, and wall shear stress inside the aneurysm sac [ 16 ]. These findings provide valuable insights that can help predict the occurrence of ruptured AAA.…”
Section: Discussionmentioning
confidence: 99%
“…EVAR within a hostile neck anatomy, particularly in short and severe neck angulation, is associated with poor early and late outcomes [ 3 , 5 ]. One study of AAA with severely angulated necks revealed significant changes in velocity, flow streamline, pressure, and wall shear stress inside the aneurysm sac [ 16 ]. These findings provide valuable insights that can help predict the occurrence of ruptured AAA.…”
Section: Discussionmentioning
confidence: 99%
“…EVAR within a hostile neck anatomy, particularly in short severe neck angulation, is associated with poor early and late outcomes [3,5]. One study of AAA with severely angulated necks revealed significant changes in velocity, flow streamline, pressure, and wall shear stress inside the aneurysm sac [16]. These findings provide valuable insights that can help predict the occurrence of ruptured AAA.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, this PC-MRI-based volumetric flow was converted to a corresponding velocity waveform and applied as an inlet boundary condition for each patient (an example shown for P1 in Figure 3). A zero-reference pressure was imposed at the outlet boundaries [14,[39][40][41]. The temporal variations of the physiological velocity inlet condition were reproduced by Fourier series and implemented through a "user_defined_function" (UDF) script.…”
Section: Patient Specific Cfd Simulationmentioning
confidence: 99%